PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MELALUI PROBLEM BASED LEARNING - Iffah Sakinah (Jurnal Edukasi dan Penelitian Matematika, 2022)
Numerical critical thinking capacity is one of capacities that is supposed to be grow ideally for students. Nonetheless, numerical critical thinking capacity of understudies in eighth grade at MTsM Saning Bakar is still low. One of the learning approach that can take care of this issue is Probelm Based Learning approach.The points of this exploration isto know whether numerical critical thinking capacity of understudies who concentrate by Probelm Based Learning  approach is superior to customary learning in eighth grade at MTsM Saning Bakar. The sort of this exploration was semi eksperiment with static grup plan. The examples of this exploration was the understudies at class VIII.B and class VIII.C. The aftereffect of the exploration show that numerical critical thinking capacity of understudies who concentrate by Issue Based Learning approach is superior to customary learning.Keywords—conventional learning,mathematical problem solving ability of students,  Probelm Based Learning  approach